PENETAPAN HAK PERWALIAN ANAK DIBAWAH UMUR PADA KASUS PERCERAIAN DALAM PERKAWINAN CAMPURAN WARGA NEGARA INDONESIA DAN WARGA NEGARA ASING - TIURLAN SIHALOHO (PREMISE LAW JURNAL, 2015)
Guardianship can accur in marriage when there is a divorce or the death of  one of the couple who is bound in wedlock. Before it occurs, the children are under their parents’ care, but if the parents are not responsible for them or do not take their repsponsibility to take care of them, the parents’ rights in the children are abolished. The requirements for the receiver of guardianship right are stipulated in the Civil Code, in the Marrieage Law, and in the Child Protection Law. The guardianship for children is in the hand of the judge when it is caused by a divorce. The consideration upon a guardianship right will be given. The right and the authority of a guardian on a child are equal to biological parents. The right includes the child personally and his property. The right of guardianship does not stop by determining who will have the right to be the guardian, either his biological father or his biological mother, through the Court’s valid verdict (inkracht). The task and the obligation of the Court in executing guardianship right do not only hand over the child to the guardian but also considers the child’s subsistence. Keywords: Mixed Marriage, Divorce, Citizenship, Guardianship Right, Guardian’s Responsibility, Execution of Guardianship